2021
DOI: 10.1111/luts.12405
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of mirabegron in treating ureteral stent‐related symptoms: A systematic review and meta‐analysis

Abstract: Objectives This meta‐analysis aimed to assess the efficacy and safety of mirabegron in treating ureteral stent‐related symptoms. Methods MEDLINE, EMBASE, and the Cochrane Controlled Trials Register were searched to identify randomized controlled trials (RCT) of mirabegron in treating ureteral stent‐related symptoms. We conducted a systematic review and meta‐analysis based on the eligible RCT. Results Five RCT including 546 patients and comparing mirabegron with placebo or blank control were involved in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Mirabegron, a β3 adrenergic receptor agonist, is recommended as an alternative treatment for SRSs with muscarine antagonist monotherapy ( Sacomani et al, 2019 ). It significantly benefits the treatment of ureteral SRSs when compared to placebo or blank control ( Li et al, 2022 ; Van Besien et al, 2022 ). A recent study has suggested that mirabegron has a favorable balance of efficacy and tolerability ( Kelleher et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mirabegron, a β3 adrenergic receptor agonist, is recommended as an alternative treatment for SRSs with muscarine antagonist monotherapy ( Sacomani et al, 2019 ). It significantly benefits the treatment of ureteral SRSs when compared to placebo or blank control ( Li et al, 2022 ; Van Besien et al, 2022 ). A recent study has suggested that mirabegron has a favorable balance of efficacy and tolerability ( Kelleher et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%